2005
DOI: 10.1145/1053291.1053320
|View full text |Cite
|
Sign up to set email alerts
|

The e-transformation of western China

Abstract: B y R o b e r t M . D a v i s o n , D o u g l a s R . V o g e l , a n d R o g e r W . H a r r i s 62

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 3 publications
(2 reference statements)
0
14
0
Order By: Relevance
“…Dependent variables posited are ones commonly utilized in studies of technology availability and utilization for countries and subnational units: personal computers (Danowitz, Nassef, and Goodman 1995;Igbaria and Iivari 1999;Meng and Li 2002;Wallsten 2005;Quibria et al 2003;Mariscal 2005;Pick and Azari 2008;Chinn and Fairlie 2007;Fong 2009), Internet users (Meng and Li 2002;Quibria et al 2003;Chinn and Fairlie 2007;Pick and Azari 2008;Lengsfeld 2011), broadband users (Yates, Gulati, and Weiss 2011), mobile phone users or subscribers (Meng and Li 2002;Quibria et al 2003;Fong 2009;Pick and Azari 2008;Song 2008;Fong 2009), and fixed phone users or subscribers (Meng and Li 2002;Kshetri and Cheung 2002;Fong 2009). The pertinence of these dependent variables for China is indicated by their inclusion in studies on the country's technology growth (Zhu and Wang 2005;Davison, Vogel, and Harris 2005;Guo and Chen 2005;Qiu 2010). Two Webbased dependent variables are included: number of domain names and number of web pages.…”
Section: A Conceptual Model Of Technology Availability and Utilizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Dependent variables posited are ones commonly utilized in studies of technology availability and utilization for countries and subnational units: personal computers (Danowitz, Nassef, and Goodman 1995;Igbaria and Iivari 1999;Meng and Li 2002;Wallsten 2005;Quibria et al 2003;Mariscal 2005;Pick and Azari 2008;Chinn and Fairlie 2007;Fong 2009), Internet users (Meng and Li 2002;Quibria et al 2003;Chinn and Fairlie 2007;Pick and Azari 2008;Lengsfeld 2011), broadband users (Yates, Gulati, and Weiss 2011), mobile phone users or subscribers (Meng and Li 2002;Quibria et al 2003;Fong 2009;Pick and Azari 2008;Song 2008;Fong 2009), and fixed phone users or subscribers (Meng and Li 2002;Kshetri and Cheung 2002;Fong 2009). The pertinence of these dependent variables for China is indicated by their inclusion in studies on the country's technology growth (Zhu and Wang 2005;Davison, Vogel, and Harris 2005;Guo and Chen 2005;Qiu 2010). Two Webbased dependent variables are included: number of domain names and number of web pages.…”
Section: A Conceptual Model Of Technology Availability and Utilizationmentioning
confidence: 99%
“…The model also includes screening for geographical clustering of like-valued estimation errors, which allows for monitoring and control of consistently overestimated or underestimated outcome values for spatial clusters within the overall geographic area of investigation (Longley et al 2011;Rosenshein, Scott, and Platt 2011). This is necessary because study after study have demonstrated the strong clustering of high technology use in China's East and low technology availability and utilization in the West (Meng and Li 2002;Loo 2003;Davison, Vogel, and Harris 2005;Song 2008). In the framework, nonrandomness in geographic patterns of estimation errors is screened for, in order to lower or avert the risk of large geographically biased estimation outcomes (Longley et al 2011).…”
Section: Conceptual Model and Research Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some regions are out of reach of privilege due to distance. Davidson et al (2005) have found that lack of infrastructure (both physical and financial) is as much an impeding factor for e-transformation there, as it is in China as a whole. Consequently, Western China's etransformation is seen to be dependent on developments in China and relationships…”
Section: Global Transformational Initiativesmentioning
confidence: 99%